ASEAN-CHINA FREE TRADE AGREEMENT (ACFTA) DAN REALITAS KESIAPAN SUMBER DAYA MANUSIA INDONESIA - Nawawi Nawawi (Masyarakat Indonesia, 2010)
This paper discusses the challanges of ACFTA, and the rise of Chinas economy which relies heavily on its human resource development threatening the position of Indonesia in the global economy. An important question is whether ACFTA can become a profitble momentum for Indonesia to enhance its national welfare, or whether it could weaken national economic sovereignity? It is largely believed that one of the most important aspects to gain optimum benefit from global competition is the readiness and the competitivenes of human resources, particularly through the development of technologies and sciences. In this context investment in human capital will lead every country to benefit from globalization. Therefore, of all the challanges faced in ACFTA, problems occured to Indonesias human resource development should be put as national priority.